Design and Analysis of Honeycomb based Impact Attenuator - Malik, Praveen; Lepsik, Petr (Manufacturing Technology Journal, 2020)
The main idea of this research work is to understand the energy absorbing capacity of cellular solids when used in application of automobile as a safety measure to protect the occupants and structure of the vehicle. The full scaled model of the proposed design of the impact attenuator would be an expensive approach to follow. To understand the mechanism of energy absorption in honeycomb structure two types of experimental test were carried out. The first test includes a simple compression test of honeycomb structure only. The second experimental test consist of a composite sandwich of glass fiber and honeycomb under high speed drop test. Using the simple compression test the mechanical properties of the honeycomb were extracted in the out of plane behavior and then results from experimental data were calibrated with the FEM model. It was observed that very similar results were obtained in Experimental and FEM methods. And finally, the full scaled model analysis was carried in FEM package of ANSYS using mechanical properties of honeycomb extracted in simple compression test.
Keywords: Impact attenuator; Compression; Energy Absorbing; Cellular Solids.